Novel Therapies for Parkinsonian Syndromes–Recent Progress and Future Perspectives - Przewodowska, Dominika; Marzec, Weronika; Madetko, Natalia (Frontiers in Molecular Neuroscience, 2021)
Background: Atypical parkinsonian syndromes are rare, fatal neurodegenerative diseases associated with abnormal protein accumulation in the brain. Examples of these syndromes include progressive supranuclear palsy, multiple system atrophy, and corticobasal degeneration. A common clinical feature in parkinsonism is a limited improvement with levodopa. So far, there are no disease-modifying treatments to address these conditions, and therapy is only limited to the alleviation of symptoms. Diagnosis is devastating for patients, as prognosis is extremely poor, and the disease tends to progress rapidly. Currently, potential causes and neuropathological mechanisms involved in these diseases are being widely investigated. Objectives: The goal of this review is to summarize recent advances and gather emerging disease-modifying therapies that could slow the progression of atypical parkinsonian syndromes. Methods: PubMed and Google Scholar databases were searched regarding novel perspectives for atypical parkinsonism treatment. The following medical subject headings were used: “atypical parkinsonian syndromes—therapy,” “treatment of atypical parkinsonian syndromes,” “atypical parkinsonian syndromes—clinical trial,” “therapy of tauopathy,” “alpha-synucleinopathy treatment,” “PSP therapy/treatment,” “CBD therapy/treatment,” “MSA therapy/treatment,” and “atypical parkinsonian syndromes—disease modifying.” All search results were manually reviewed prior to inclusion in this review. Results: Neuroinflammation, mitochondrial dysfunction, microglia activation, proteasomal impairment, and oxidative stress play a role in the neurodegenerative process. Ongoing studies and clinical trials target these components in order to suppress toxic protein accumulation. Various approaches such as stem cell therapy, anti-aggregation/anti-phosphorylation agent administration, or usage of active and passive immunization appear to have promising results. Conclusion: Presently, disease-modifying strategies for atypical parkinsonian syndromes are being actively explored, with encouraging preliminary results. This leads to an assumption that developing accurate, safe, and progression-halting treatment is not far off. Nevertheless, the further investigation remains necessary.